Iron supplementation has minor effects on gut microbiota composition in overweight and obese women in early pregnancy. Issue 3 (23rd May 2018) - Dekker Nitert, Marloes; Gomez-Arango, Luisa F.; Barrett, Helen L.; McIntyre, H. David; Anderson, Gregory J.; Frazer, David M.; Callaway, Leonie K.
Abstract: Fe is an essential nutrient for many bacteria, and Fe supplementation has been reported to affect the composition of the gut microbiota in both Fe-deficient and Fe-replete individuals outside pregnancy. This study examined whether the dose of Fe in pregnancy multivitamin supplements affects the overall composition of the gut microbiota in overweight and obese pregnant women in early pregnancy. Women participating in the SPRING study with a faecal sample obtained at 16 weeks' gestation were included in this substudy. For each subject, the brand of multivitamin used was recorded. Faecal microbiome composition was assessed by 16S rRNA sequencing and analysed with the QIIME software suite. Dietary intake of Fe was assessed using a FFQ at 16 weeks' gestation. Women were grouped as receiving low (<60 mg/d, n 94) or high (≥60 mg/d; n 65) Fe supplementation. The median supplementary Fe intake in the low group was 10 (interquartile range (IQR) 5–10) v . 60 (IQR 60–60) mg/d in the high group ( P <0·001). Dietary Fe intake did not differ between the groups (10·0 (IQR 7·4–13·3) v . 9·8 (IQR 8·2–13·2) mg/d). Fe supplementation did not significantly affect the composition of the faecal microbiome at any taxonomic level. Network analysis showed that the gut microbiota in the low Fe supplementation group had a higher predominance of SCFA producers. Pregnancy multivitamin Fe content has a minor effect on the overall composition of the gut microbiota of overweight and obese pregnant women at 16 weeks' gestation.